Geochemical researches of the Marmarosh massif of the Ukrainian Carpathians - Крюченко, Наталія Олегівна; Жовинський, Едуард Якович; Папарига, Петро Степанович (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2020)
Formulation of the problem. The main focus of our research is on the geochemical composition of the growth areas of beech forests in the Marmarosh Massif of the Ukrainian Carpathians, or primeval forests, which are almost unaffected by human activity. Geochemical investigations of beech forests are especially important, since the question of chemical component of environmental objects (soils, vegetation) is the basis for determining the degree of territories transformation in time. The Carpathians belong to one of the most studied metallogenic provinces. The ore occurrence contains natural gold, silver and silver minerals (sulfates, sulfides, hydrosulfides) associated with pyrite, chalcopyrite, arsenopyrite, pyrrhotite, marcasite, hematite, galena, and other. It is important to determine the background content of chemical elements in soils, which will become the basis for geochemical searches and the determination of pollution - "reference point", which should be relied upon when conducting environmental and geochemical studies in the territory of beech virgin forests. The purpose of the article. The purpose of this work is to determine the background gross content of chemical elements (Mn, Ni, Co, Ti, V, Cr, Mo, W, Zr, Hf, Rb, Ta, Cu, Pb, Ag, Sb, Bi, Zn, Cd, Sn, Ge, Ga, Be, Sc, Ce, La, Y, Yb, Th, As, Ba, Li, P) and the main mobile forms of metals - Cu, Pb, Zn in soils of forest ecosystems of beech forests of the Marmarosh Massif; determination of biogeochemical features of the concentration of chemical elements by vegetation - beech leaves, Hypericum L., Achillea millefolium, Boletus edulis, which will become the basis for monitoring studies. Methods. Lithochemical, biogeochemical testing was carried out. The gross content of chemical elements (emission spectral analysis) and mobile forms of metals (atomic absorption analysis) was determined. Results. The authors calculated the background values of chemical elements content in the soils of forest ecosystems of beech protected areas of the Marmarosh Massif. In conducting lithochemical studies, chemical elements (gross content) – Co, Ni, V, Cu, Zn, Pb, P, Mn, Ti, whose contents are higher in soils, where carbonate rocks are soil-forming and in the absence of carbonates - Cr, Mo, have been established Zr, Sn, Be. La, Y, Yb, Ba, Li. The main moving forms of metals in soils (Cu, Pb, Zn) were determined and their coefficients of mobility were calculated, on the basis of which it was established that the mobility of metals in soils where soil-forming rocks are granite-gneisses and sandstones higher than in soil-soils is 3–10 times, in addition, the pH value of soils is a dominant factor in solving the migration or concentration of metals and the formation of secondary salt halos in the presence of ore. An analysis of the chemical composition of the indicator vegetation and its parts – Hypericum L, Achillea millefolium and Boletus edulis in the area of Mount Figura was performed. Boletus edulis, St. Hypericum L, wort stems and yarrow Achillea millefolium are identified as Cu, Zn concentrators. This distinction is important when conducting biogeochemical studies with a search purpose. Scientific novelty and practical significance. The results of the conducted researches showed that the regularities of distribution of chemical elements and their mobile forms in soils and vegetation in different parts of the Trans Carpathian forest ecosystems can be the basis for the exploration, forecasting the ecological status of the territories and, in general, ecological and geochemical monitoring.